Simultaneous use of shape memory alloys and permanent magnets in multistable smart structures for morphing aircraft applications - Sales, Thiago de Paula (2017)
This Thesis considers the simultaneous use of shape memory alloys and permanent magnets for achieving multistable smart structures aiming towards morphing applications. Motivation for this approach lies in the poor energetic efficiency of shape memory alloys, which can void system-level benefits provided by morphing technologies. Multistability can therefore be adopted to prevent continuous operation of shape memory alloy actuators. Objectives of the study involve the combination of shape memory alloys and permanent magnets in new geometrical arrangements to achieve multistable behavior; the development of a numerical modeling procedure that is able to simulate the multi-physics nature of the studied systems; and the proposal of a geometric arrangement for morphing applications that is based on a repeating pattern of unit cells which incorporate the combined use of shape memory alloy wires and permanent magnets for multistability. The proposed modeling strategy considers a geometrically nonlinear beam finite element; a thermo-mechanical constitutive behavior for shapememoryalloys;theinteractionofcuboidalpermanentmagnetswitharbitraryorienta- tions; and node-to-element contact. Experiments are performed with three distinct systems, including a proof-of-concept beam, a three cell morphing beam metastructure, and a morphing airfoil prototype with six unit cells. Results show that the combination of shape memory alloys and permanent magnets indeed allows for multistable behavior. Furthermore, the dis- tributedactuationcapabilitiesofthe morphingmetastructureallowforsmoothandlocalized geometrical shape changes.